Mad City - Gavras, Costa (Warner Bros, 1997)
A freeway pursuit. A domestic spat gone over the edge. You've watching it live at home, news as it happens. But wait a minute. Is the reporter on your TV screen shaping the story, extending its life, making it happen? Dustin Hoffman and John Travolta team with award-winning filmmaker Costa-Gavras (Z, Missing) in a fierce tale of ratings-driven TV news gone mad. Travolta is Sam, a misguided museum guard who loses his job, then tries to get it back at gunpoint. Hoffman is Max, a local TV reporter taken hostage with a group of schoolchildren when Sam locks down the museum. It's a desperate move for Sam, a career move for Max. He's on the inside of a live exclusive. Now all he has to do is give Sam's story a heroic spin, Keep a headline-grabbing network anchor at bay and above all. keep America watching. And as Max pulls the strings even tighter, the stakes grow higher, darker, madder.
Keywords: Drama; Action